Reply to letter to editor by Hadigal et al. regarding the immunogenicity and safety trial of high-dose influenza vaccine in adults aged ≥60 years - J. Kevin Yin; Stephanie Pepin; Robertus van Aalst; Matthew M. Loiacono; Sandrine I. Samson (Taylor & Francis Group, 2022)
Hadigal et al. argued the recommendation of high-dose influenza vaccine over standard-dose formulation is not supported by comparisons of numbers-needed-to-vaccinate (NNV) nor aligned with the WHO mandate of improving vaccine coverage. However, the authors' NNV calculation was inaccurate. A preferential recommendation for vaccines preventing influenza/complications can increase coverage. Furthermore, the impact of vaccination is a function of efficacy/effectiveness and the vaccine-preventable fraction of disease burden; therefore Hadigal et al. should interpret the absolute risk reduction by vaccination within the context of overall disease burden. To address the threat of COVID-19 pandemic, authorities should implement concomitant influenza/COVID-19 vaccination to reduce the burden of cocirculation of influenza and SARS- CoV- 2 viruses and increase the coverage of proven influenza vaccines as per WHO mandate.